'Spirited bodies' as a prerequisite for an earth-keeping ethos : a juxtaposition on the first creation story of Genesis with ubuntu cosmogony - Buitendag, Johan (University of Pretoria, 2014)
Dissertation (MA Theol)--University of Pretoria, 2013.